2023
DOI: 10.3233/ch-221680
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of ultrasound-guided core needle biopsies (US-CNBs) in cervical lymphadenopathy in patients with suspected head and neck cancer during the COVID-19 pandemic

Abstract: BACKGROUND: Cervical lymphadenopathy can be benign or malignant. Its accurate diagnosis is necessary to determine appropriate treatment. Ultrasound-guided core needle biopsies (US-CNBs) are frequently used as a percutaneous sampling approach. OBJECTIVES: Our aim was to identify the efficacy and safety of US-CNBs in 125 patients with cervical lymphadenopathy and clinically suspected head and neck cancer during the COVID-19 pandemic with limited surgical resources. METHODS: US-CNBs of pathological lymph nodes we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…The need for adjuncts such as immunohistochemistry in deciding treatment for the patients as in the case of lymphomas or for deciding the intensity of treatment and prognosis as in the case of p16 status in oropharyngeal carcinoma or to aid in finding the primary in nodal metastasis with occult primary would favour a core needle biopsy over FNAC 10,11 . Many studies have shown ultra sound guided core biopsy to be a safe and efficient investigation and has a very low risk of tumour seeding or damage to surrounding structures 12 . As FNAC yields only a very small sample, it is often inadequate for immunocytology which again is not as sensitive as immunohistochemistry and up to 37% patients would often need further FNAC or core biopsy following FNAC 5 .…”
Section: Discussionmentioning
confidence: 99%
“…The need for adjuncts such as immunohistochemistry in deciding treatment for the patients as in the case of lymphomas or for deciding the intensity of treatment and prognosis as in the case of p16 status in oropharyngeal carcinoma or to aid in finding the primary in nodal metastasis with occult primary would favour a core needle biopsy over FNAC 10,11 . Many studies have shown ultra sound guided core biopsy to be a safe and efficient investigation and has a very low risk of tumour seeding or damage to surrounding structures 12 . As FNAC yields only a very small sample, it is often inadequate for immunocytology which again is not as sensitive as immunohistochemistry and up to 37% patients would often need further FNAC or core biopsy following FNAC 5 .…”
Section: Discussionmentioning
confidence: 99%